2023
DOI: 10.1177/00144029221148784
|View full text |Cite
|
Sign up to set email alerts
|

Unequal and Increasingly Unfair: How Federal Policy Creates Disparities in Special Education Funding

Abstract: The formula used to allocate federal funding to states for special education is one of IDEA's most critical components. The formula serves as the primary mechanism for dividing available federal dollars among states and represents policy makers’ intent to equalize educational opportunities for students with disabilities nationwide. In this study, we evaluate the distribution of IDEA Part B funding in the wake of changes to the formula that were instituted at the law's 1997 reauthorization. We find that the rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Next, Kolbe and colleagues (2023) evaluate the distribution of the Individuals With Disabilities Education Act (IDEA) Part B funding following revisions to the formula instituted in IDEA's 1997 reauthorization. The authors concluded that the revised formula has contributed to disparities among states in federal special education dollars, finding that states with larger populations of children and children living in poverty, children identified for special education, and children of color receive fewer federal dollars per capita.…”
Section: Introduction To the Articles In This Issuementioning
confidence: 99%
“…Next, Kolbe and colleagues (2023) evaluate the distribution of the Individuals With Disabilities Education Act (IDEA) Part B funding following revisions to the formula instituted in IDEA's 1997 reauthorization. The authors concluded that the revised formula has contributed to disparities among states in federal special education dollars, finding that states with larger populations of children and children living in poverty, children identified for special education, and children of color receive fewer federal dollars per capita.…”
Section: Introduction To the Articles In This Issuementioning
confidence: 99%